China's battle for Korea the 1951 spring offensive - Li, Xiaobing 1954- (Indiana Univ. Press, 2014)
"More than fifty years ago, the United States sent troops into Korea as part of a United Nations Command to check the North Korean invasion of South Korea. After repelling the invasion, the UN forces crossed the 38th parallel and approached the Yalu River, the Chinese-North Korean border. Leaders of the People's Republic of China considered the UN action to be a challenge to the newly-established Communist regime and launched an invasion "to resist America and aid Korea." Between November 1950 and the end of the war in June 1953, the Chinese People's Volunteer Army launched six major offensives against the UN forces. The most important of these, the fifth, began on April 22, 1951, and was the greatest Communist military operation of the war, the largest battle since the end of World War II. The Chinese deployed more than 700,000 men, including 600,000 troops in 33 infantry and four artillery divisions. The engagement lasted more than five weeks. The UN forces put up a strong defense and stopped the Chinese short of the South Korean capital of Seoul. The Chinese never again came so close to Seoul. China's defeat in this battle forced Mao Zedong to reconsider his aims on the battlefield, and the Chinese leadership became willing to conclude the war short of total victory. Battle for Korea offers new perspectives on Chinese decision-making, planning, and execution; the roles of command, political control, and technology; and the interaction between Beijing, Pyongyang, and Moscow, and it provides valuable insight into Chinese military doctrine and the reasons for the UN's military success"..
Includes bibliographical references (pages 351-369) and index
Keywords: Geschichte 1951; HISTORY / Military / Korean War; Koreakrieg; Korean War, 1950-1953 -- Participation, Chinese; Korean War, 1950-1953 -- Campaigns; China